An industrial systems design study on Manly Plastics, Inc. - Ricafrente, Joanne L.; Romero, Maricelle G.; Villegas, Camilla Natasha B. (Diliman, Quezon City College of Engineering, 2001)
Supply Chain Management is one of the most important issues in business today. The idea is to apply a total systems approach to managing the entire flow of information, materials, and services from raw-materials suppliers through factories and warehouses to the end customer. Manly Plastics, Inc. is a manufacturing firm which produces plastic components for electrical appliances such as refrigerators, air conditioning units, and television sets, as well as crates and other packaging containers. Originally a simple tool and die shop with only 8 employees located on a 400-square meter plant in Royal St., Barrio Kangkong, Quezon City, Manly has evolved into a 7 plant group of ISO 902 certified companies. It now serves some 15 countries around the world for the injection-moulded plastic components of the appliance, electronics, communication and house ware manufacturing industries. It is very surprising that, though Manly Plastics, Inc is a relatively established company already, it still encounters numerous problems associated and linked with issues concerning the supply chain. To help Manly Plastics, Inc. address these issues, an Industrial Systems Design Study is conducted. The primary goal of this project study is to optimize the resources involved in the company's supply chain. The three components of the supply chain which have been given attention re: Inbound Logistics, Manufacturing, and Outbound Logistics. In identifying and analyzing the problems encountered by the company, different tools - such as the SAPADAPPA (Situation Appraisal, Problem Analysis, Decision Analysis and Potential Problem Analysis), Failure Mode and Effects Analysis, Streamline Analysis, Process Analysis Map and Pareto Analysis ? were used. From these, four major concerns were determined. These primary issues which have been facing Manly Plastics, Inc. are: 1) absence of inventory planning, 2) ineffective supplier selection process, 3) inappropriate stock locator system, and 4) unsophisticated information system. To solve these problems, various alternative solutions were evaluated using a set of criteria. For the problem on inventory planning, a Co-Managed inventory system is recommended. Also, a more appropriate stock locator system, which is Fixed storage (for each customer) and Storage based on ABC (for each customer cell), is proposed. On the issue of supplier selection, improvements on the evaluation criteria are suggested, as well as the establishment of Supplier Partnerships / Agreements. The installation and implementation of Enterprise Resource Planning (ERP) Software, particularly MFG/PRO, is also proposed to facilitate a company-wide integrated information system. From this study, it can be concluded that companies should give considerable attention to Supply Chain Management, since it can very well determine the success or failure of a firm.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 155 : Industrial Systems Design
Keywords: Manly Plastics, Inc; Plastics industry and trade; Delivery of goods--Management.; Business logistics; Customer services--Management.; Physical distribution of goods--Management.; Inventory control; System design